Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Pelanggan KRL Commuterline Rute Jakarta Kota – Bogor - Dickdick Sodikin (JAMBIS : Jurnal Administrasi Bisnis, 2023)
PT. Kereta Commuter Indonesia is a popular mode of public transportation for Indonesians. This study aims to determine how much influence the quality of service and facilities has on customer satisfaction of the KRL commuter line from Jakarta Kota to Bogor. The research is quantitative, and a simple random sampling technique was used. Questionnaires were distributed to 100 respondents to obtain the research data. Multiple regression was used to analyze the data. The results showed that the service quality variable (X1) had a positive and significant effect, with 56.2% customer satisfaction. The facility variable (X2) had a positive and significant effect, with 58.6% customer satisfaction. Besides, the quality of service and facilities jointly affect customer satisfaction by 64.9%.